Health-care productivity, and its sociodemographic determinants, of Saudi female nurses:: A cross-sectional survey, Al-Qassim, Saudi Arabia, 2017 - Altakroni, Hassan; Mahmud, Ilias; Emossad, Yousif Mohammed; Al-Akhfash, Ali; Al-Hindi, Adel; Joshva, Kavija (International Journal of Health Sciences, 2019)
Background: In Saudi Arabia, cultural and language differences between expatriate nurses and patients affect the quality of nursing care. Hence, the Kingdom is eying Saudization in this field. The productivity of nurses can affect the productivity of the whole health system. The aim of this study was to investigate the health-care productivity of Saudi female nurses and socio-demographic determinants of their productivity. Methods: We conducted a cross-sectional survey of 256 randomly selected Saudi female nurses in the Qassim region. The nurses who were not working in public hospitals; not giving direct patient care or had <1-year patient-care experience were excluded from the study. The nurses’ work productivity was measured using a 17-item index. Results: The mean age of the nurses was 30.2 ± 5.6 years. Among the nurses, 62.6% were currently married, 33% were never married, and 4.4% were divorced/widowed. Most of the nurses were not willing to serve male patients (70.3%); they wanted to work only in female units (66.1%) and did not prefer night shifts (50.8%). Over the past 1 year, most of them demonstrated tendency of taking emergency leave (64.2%) and sick leave (56.4%), while 27.3% had unexcused absences and 19.5% had unplanned but excused absences. In addition, 20.3% demonstrated a tendency of taking frequent breaks during duty hours and 18.9% demonstrated tendency of being late on duty. Multivariable linear regression analysis revealed that being married was associated with 1.66 points decrease in the productivity index score when compared to never married nurses. Having one more child under 5 years of age was associated with 0.75 points increase in the productivity index score. In addition, nurses who employed household workers at home scored 1.04 points less than those who did not. Conclusions: Health-care productivity index score was lower among married Saudi female nurses than never married nurses. However, aspects of married life commonly believed to cause home work-life conflicts, such as number of children, living with or without family, having disabled children in household and personal factors such as age did not have statistically significant influence on the productivity index score. It is possible that unexplained cultural issues associated with being married may be responsible for a lower productivity index score among married female nurses in Saudi Arabia.